2013
DOI: 10.1097/inf.0b013e31829be4bc
|View full text |Cite
|
Sign up to set email alerts
|

Oseltamivir Treatment for Influenza in Hospitalized Children Without Underlying Diseases

Abstract: There were no proven benefits of treatment with oseltamivir in hospitalized pediatric patients without the underlying diseases or risk factors for developing a serious illness, including those with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…All the studies in our systematic review included broad populations, and so subset data on people with cardio‐pulmonary conditions were extracted according to our predetermined inclusion criteria. The subset data from three studies were from patients with asthma, 11,26,27 and two were from those with cardio‐pulmonary conditions 25,28,29 . Two studies defined their high‐risk population as those with chronic cardio‐pulmonary conditions and/or the elderly and as individual data were not available, the whole population was included 30,31 .…”
Section: Resultsmentioning
confidence: 99%
“…All the studies in our systematic review included broad populations, and so subset data on people with cardio‐pulmonary conditions were extracted according to our predetermined inclusion criteria. The subset data from three studies were from patients with asthma, 11,26,27 and two were from those with cardio‐pulmonary conditions 25,28,29 . Two studies defined their high‐risk population as those with chronic cardio‐pulmonary conditions and/or the elderly and as individual data were not available, the whole population was included 30,31 .…”
Section: Resultsmentioning
confidence: 99%
“…23,24 A study of 287 hospitalized, previously healthy children found no difference in length of stay, diagnosis of pneumonia, ICU admission or death in NAItreated compared with untreated patients; however, the young age of patients (40% aged ,6 months) may have prompted hospitalization for observation purposes rather than because of severity of illness. 25 A retrospective cohort study of .500 children with severe seasonal influenza illness admitted to PICUs over 6 influenza seasons (2001)(2002)(2003)(2004)(2005)(2006)(2007) found that patients treated with oseltamivir within 24 hours of hospital admission had an 18% reduction in total hospital days (P = .02) but no significant reduction in length of PICU stay, in-hospital mortality, and readmission rates. 26 In contrast, a handful of small studies have suggested that early NAI treatment improves survival.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospectively, there were no proven benefits for oseltamivir in hospitalized pediatric patients without underlying diseases or risk factors for developing a serious illness, including those with asthma [70]. Also the Cochrane meta-analysis, mainly based on 1 poorly designed study, described no significant benefit for oseltamivir treatment in children with pneumonia, although it might reduce the symptoms earlier, without other clinical relevance [71].…”
Section: Oseltamivirmentioning
confidence: 99%